2018
DOI: 10.3390/s18020412
|View full text |Cite
|
Sign up to set email alerts
|

Development of Wind Speed Retrieval from Cross-Polarization Chinese Gaofen-3 Synthetic Aperture Radar in Typhoons

Abstract: The purpose of our work is to determine the feasibility and effectiveness of retrieving sea surface wind speeds from C-band cross-polarization (herein vertical-horizontal, VH) Chinese Gaofen-3 (GF-3) SAR images in typhoons. In this study, we have collected three GF-3 SAR images acquired in Global Observation (GLO) and Wide ScanSAR (WSC) mode during the summer of 2017 from the China Sea, which includes the typhoons Noru, Doksuri and Talim. These images were collocated with wind simulations at 0.12° grids from a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
25
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 33 publications
(26 citation statements)
references
References 39 publications
1
25
0
Order By: Relevance
“…It is highly effective for monitoring the Earth’s environments, measuring significant wave heights, wind speeds, soil moisture, and ice and snow thicknesses [ 2 , 3 , 4 , 5 ]. In particular, the characteristics of wind speed are an important factor for the observations of typhoon and hurricane events [ 6 , 7 ]. In 2003, Surrey Satellite Technology developed the first GPS-R receiver onboard the UK-Disaster Monitoring Constellation (UK-DMC) satellite in order to establish ocean and land surface conditions [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…It is highly effective for monitoring the Earth’s environments, measuring significant wave heights, wind speeds, soil moisture, and ice and snow thicknesses [ 2 , 3 , 4 , 5 ]. In particular, the characteristics of wind speed are an important factor for the observations of typhoon and hurricane events [ 6 , 7 ]. In 2003, Surrey Satellite Technology developed the first GPS-R receiver onboard the UK-Disaster Monitoring Constellation (UK-DMC) satellite in order to establish ocean and land surface conditions [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…Since 1978, synthetic aperture radar (SAR) images with advantages of high spatial resolution, large spatial coverage, and the capability of sensing through clouds at day and night have become available for studying, forecasting, and monitoring TCs (Li 2015;Yu et al 2017). With development of SAR technology, the TC wind speed retrieval by C-band SAR is widely studied from copolarization signals to cross-polarization (CP) signals (Zhang and Perrie 2014;Hwang 2016;Shao et al 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Generally, TC sea surface wind speed can be retrieved either from normalized radar cross section (NRCS) directly (Zhang and Perrie 2014;Zhang et al 2017) or from the SAR-derived wave information indirectly (Hwang 2016;Shao et al 2017). For TC conditions, due to the saturation of the drag coefficient, aerodynamic roughness, and sea surface roughness (Donelan et al 2004;Bye and Jenkins 2006;Fujimura et al 2019), the copolarization NRCS starts to saturate and decreases as wind speed increases beyond marginal hurricane strength (Hwang et al 2010;Hwang and Fois 2015).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Yin et al [ 3 ] provided an analysis on the physical scattering mechanism of GF-3 polarimetric SAR data and showed that the data has great potential for target characterization. Shao et al [ 4 ] developed the method of strong wind retrieval from the cross-polarization GF-3 SAR data. Chang et al [ 5 ] had an experiment on the calibration of residual polarimetric distortion for channel imbalance and crosstalk of GF-3 polarimetric SAR images and improved the quality of image greatly.…”
Section: Introductionmentioning
confidence: 99%